Selected Sources of Financing Investment in Water and Sewage Management in Poland - Rosiek, Ksymena (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
One of the challenges contemporary economies face is to ensure a sufficient supply of optimal quality water for different user needs while at the same time preserving the principles of ecosystem protection. Poland deals with a significant developmental and civil challenge in this area, mainly due to previous negligence in sewage management. When it joined the European Union, Poland assumed certain obligations in this area resulting from the implementation of the so-called Sewage Sludge Directive and the Water Framework Directive. At the same time, the EU budget designated financial resources to facilitate quicker achievement of the appropriate objectives. It is therefore revealing to track changes in the area of water and sewage management, especially those involving the share of funds from abroad and budgetary commitments of individual municipalities used to co-finance these as well as changes in the regional provision of the relevant infrastructure. Accordingly, the aim of the paper is to analyse investment expenditure in the area of water and sewage management in Poland by region with a special focus on changes in selected sources of financing, especially funds originating from abroad and from municipality budgets.